ANALISIS KESULITAN SISWA DALAM MEMBACA PERMULAAN DI KELAS 1 SEKOLAH DASAR - Ujang Jamaludin; Sigit Setiawan; Dea Oktadri Yanti Putri; Selvi Mutia Yunita; Muhamad Afrizal (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2023)
Reading skill is an aspect that exists in the language skills of elementary school students which must always be mastered by students. Difficulty reading is also a distraction and a barrier that can hinder an aspect of students' reading ability. The purpose of this study is to analyze students' difficulties in reading beginning in grade 1 of elementary school. Researchers used qualitative research methods using qualitative descriptive types. The research location was carried out in June 2023 at SD Negeri Cimone 6, with a total of 31 students. Data collection methods that will be used by researchers are observation, interviews, and documentation. The results of the study showed that students at SDN 6 Cimone who had difficulty reading beginning were grade 1 students. The type of students' initial reading difficulty was recognizing letters with almost the same shape. Beginning reading difficulties experienced by students are caused by internal factors and external factors. Efforts made by the teacher to reduce reading difficulties in students are by providing additional hours and designing learning that increases student enthusiasm for learning.